Ländliche Neusiedlung in der Schweiz vom Ende des 19. Jahrhunderts bis zur Gegenwart - Egli, Hans-Rudolf (ERDKUNDE, 1986)
The concept of ’inner colonization’ was not current in Switzerland before 1918, because there were no large agricultural estates which could be broken up to make new farming settlements. Moreover, although the extensive marshy areas had for the most part been drained by 1914, they could not be colonized due to a farming crisis which involved the collapse of Swiss grain production in the 1870’s and 80’s. These drainage works actually laid a foundation for subsequent colonization projects, however. The food shortage during the First World War led to a commitment on the part of industrial and trading companies and their employees to raise the agricultural self-sufficiency of the population through so-called Bebauungswerken. This in turn led to the private ’Alliance for Inner Colonization and Industrial Farming’. Its founder and chairman, Hans Bernhard, influenced the Alliance and, through it, inner colonization to a great extent. Of its numerous projects (wasteland development, industrial housing estates, farming setdements, resetdement projects, etc.) only a few were realized (Fig. 3). Nor was Bernhard’s draft of a federal settlement law taken up by the Federal Council. On the other hand the ’Land-register for Inner Colonization’, begun in 1926, laid the principal ground-work for the ’Agricultural Production Register’ which was essential to the Swiss Agricultural Plan during the Second World War. The result of this plan was a twofold increase in area of arable land and, thereby, a decisive contribution to the Swiss food supply. However, inner colonization did not receive either financial or moral support from the government until 1936. The great successes of the Swiss Agricultural Plan which at least partially grew out of the efforts of inner colonization, strengthened Swiss agriculture far beyond the war years - probably even up to the present.